Lessons learned from HIV-1 vaccine trials: new priorities and directions. - Mcmichael, A; Haynes, B (2012)
A vaccine against human immunodeficiency virus (HIV) seems to be on the horizon. Correlates of risk of infection for [corrected] the RV144 vaccine trial have been found. There is understanding of what makes HIV envelope-specific antibodies broadly neutralizing and new T cell vaccine approaches can overcome virus variability.